2020
DOI: 10.29309/tpmj/2020.27.07.4273
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and missed opportunities towards immediate and early post-partum family planning methods in Pakistan.

Abstract: The postpartum family planning (PPFP) services are offered immediately after delivery (immediate PPFP), within 40 days after delivery (early PPFP) and within 12 month after delivery (extended PPFP). To promote PPFP the counselling during antenatal visit, before discharge from maternity ward, during postnatal visit and visit during immunization of their babies are the opportunities where health providers help them to decide about the post-partum contraception. Objectives: To compare the coverage of imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
2
0
0
Order By: Relevance
“…This study revealed that 21.3% (95% CI 17.8 to 25.1) of postpartum women used IPPFP, consistent with studies done in Ethiopia (19.1%–21.6%) 31–33. However, the current finding was lower than the studies conducted in Georgia (49%),34 Kenya (50.3%),35 Jimma (53.2%)5 and Addis Ababa (45.5%),36 and higher than the studies conducted in Pakistan (4%)37 and Ethiopia (12.7%–13.6%) 38 39. These variations might possibly be due to differences in sociocultural and demographic characteristics, study setting, data collection period and inclusion criteria.…”
Section: Discussionsupporting
confidence: 87%
“…This study revealed that 21.3% (95% CI 17.8 to 25.1) of postpartum women used IPPFP, consistent with studies done in Ethiopia (19.1%–21.6%) 31–33. However, the current finding was lower than the studies conducted in Georgia (49%),34 Kenya (50.3%),35 Jimma (53.2%)5 and Addis Ababa (45.5%),36 and higher than the studies conducted in Pakistan (4%)37 and Ethiopia (12.7%–13.6%) 38 39. These variations might possibly be due to differences in sociocultural and demographic characteristics, study setting, data collection period and inclusion criteria.…”
Section: Discussionsupporting
confidence: 87%
“…Respondents who sought PNC were more likely to use modern contraceptive methods. Evidence in the literature has endorsed that postnatal counseling before discharge significantly improves motivation for and practice of contraceptive uptake [26, 31, 32, 33]. This study also observed that Lady Health Worker’s counselling delivered during a PNC visit increased the likelihood of family planning utilization.…”
Section: Discussionsupporting
confidence: 57%
“…Besides these, there are common misconceptions among individuals regarding the use of IUDs, with concerns including the potential for abortion, ectopic pregnancy, and discomfort. Additionally, there are fears that the IUD may rust inside the body and become displaced during sexual intercourse, leading to sexual complications [4,29].…”
Section: Fear and Misconceptions Among Women Regarding Iudsmentioning
confidence: 99%
“…Rapid population growth can lead to the exacerbation of unemployment and a scarcity of health and education resources [4]. Also, low birth spacing, besides a characteristic of a drastic population rise, poses a greater risk for maternal and infant health issues [5].…”
Section: Introductionmentioning
confidence: 99%